Alternatives and potential for added value in community-type tourism initiatives. Lessons from the case of the Subprovince of Alto Ricaurte (Boyacá) - Dueñas Quintero, Diana María ; Universidad Pedagógica y Tecnológica de Colombia; Vianchá Sánchez, Zulma Hasbleidy ; Universidad Pedagógica y Tecnológica de Colombia; Fraile Benítez, Ana Mercedes; Universidad Pedagógica y Tecnológica de Colombia; Pérez Martínez, Rosa Nely ; Universidad Pedagógica y Tecnológica de Colombia; Castillo-Reina, Miguel Ángel ; Universidad Pedagógica y Tecnológica de Colombia; Ayala Suárez, Yesika Alejandra ; Universidad Pedagógica y Tecnológica de Colombia; Romero Benavides, Camila Andrea ; Universidad Pedagógica y Tecnológica de Colombia; Salamanca Merchán, Juan David ; Universidad de Boyacá; González González, Andrés ; Universidad de Boyacá; Ramírez Ávila, Leidy Paola ; Universidad de Boyacá (UPTC Editorial, 2021)
Despite the negative effects generated by the COVID-19 pandemic, community-based tourism is constituted as an alternative form of economic growth and development thanks to the integration of local experiences, as well as the use and conservation of natural resources, cultural and heritage. This research focused on identifying the factors that add value and how the actors involved in this kind of tourism get involved. A theoretical context and state of the art are presented in the categories of territoriality, community tourism, value chain and flow, and value co-creation processes. The results are based on the socioeconomic characterization of the Province of Alto Ricaurte in Boyacá, the analysis of the offer and the perception of tourists in the co-creation processes on the addition of value, which confirms the importance of community tourism as a process of collective construction that involves different approaches and concepts regarding how it is interpreted and how it is handled.